PEMBERIAN LAYANAN BIMBINGAN KARIER DI SMK SUNAN AMPEL MENGANTI GRESIK - Muwakhidah, Muwakhidah; Mufidah, Elia Firda; Mudhar, Mudhar; Moesarofah, Moesarofah (Universitas PGRI Adi Buana Surabaya, 2022)
Career is an important thing in the development of an individual's life. Likewise for students who undergo career stages according to the stages of development. This service focuses on providing career guidance and counseling services that are packaged in classical guidance services and career interest aptitude tests. This service is given to class XII students of SMK Sunan Ampel Menganti Gresik. From the results of the service, it is obtained a career description that has been designed by each student and the results of the career interest aptitude test which provide an explanation regarding the career personality of each student.